Replacing Lost or Damaged Papers - Regina Fegan; Michael T. Olexa (EDIS)
This document, IFAS publication DH0505, was published June 1998, revised May 2003. It is part of The Disaster Handbook, a component of the Comprehensive Disaster Preparedness and Recovery Education Module.